Associations of glycated haemoglobin A1c and glycated albumin with subclinical atherosclerosis in middle‐aged and elderly Chinese population with impaired glucose regulation. (June 2015) - Ma, Xiaojing; Shen, Yun; Hu, Xiang; Hao, Yaping; Luo, Yuqi; Tang, Junling; Zhou, Jian; Bao, Yuqian; Jia, Weiping
Summary The aim of this study was to investigate the correlations of glycated haemoglobin A1c (HbA1c) and glycated albumin (GA) with subclinical atherosclerosis in middle‐aged and elderly Chinese populations with impaired glucose regulation (IGR). In total, 640 subjects with IGR and no history of cardiovascular disease or carotid artery plaque were recruited for this study (256 men, 384 women; age range, 40–70 years). The carotid intima‐media thickness (C‐IMT) measured by carotid ultrasonography was used as an indicator of subclinical atherosclerosis. Increased C‐IMT was defined as ≥ 0.70 mm (upper quartile). HbA1c and GA were measured with high‐performance liquid chromatography and enzymatic method, respectively. The average HbA1c and GA among all 640 subjects were 5.7 ± 0.3% and 14.0 ± 1.1%, respectively. HbA1c and GA were higher in subjects with increased C‐IMT than in subjects with normal C‐IMT (5.8 ± 0.3% vs 5.7 ± 0.3% and 14.2 ± 1.0% vs 13.9 ± 1.1%, respectively; both P < 0.01). Correlation analysis showed that both HbA1c and GA were positively correlated with C‐IMT (r = 0.135 and 0.112, respectively; both P < 0.01). Logistic regression analysis revealed that both HbA1c (odds ratio (OR), 2.630; 95% confidence interval (95% CI), 1.401–4.935; P = 0.003) and GA OR, 1.215; 95% CI, 1.008–1.466; P = 0.041) were independent risk factors for increased C‐IMT. Both HbA1c and GA reflect the risk of subclinical atherosclerosis in middle‐aged and elderly Chinese populations with IGR.